2006
DOI: 10.4489/myco.2006.34.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Two Species of the Laboulbeniales from Tibet

Abstract: Two species of the Laboubeniales based on the Tibetan collections are described. They are new to the mycological flora of Tibet. Laboulbenia polyphaga found on several parts of Amara majuscula was characterized by having the outer appendages not ramified and simple. Peyritschiella protea obtained on the lower abdomen of Philonthus wuesthoffi, had two perithecia and two antheridia produced on the third layer of receptacle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…On Philonthus: Poland ), China? (Lee et al 2006), Belgium (De Kesel & Gerstmans 2011). On Phloeopora?…”
Section: Distribution and Hostsmentioning
confidence: 99%
“…On Philonthus: Poland ), China? (Lee et al 2006), Belgium (De Kesel & Gerstmans 2011). On Phloeopora?…”
Section: Distribution and Hostsmentioning
confidence: 99%
“…Recorded on the following staphylinid genera: Anotylus Thomson, 1859;Bledius Samouelle, 1819;Manda Blackwelder, 1952;Oxytelus Gravenhorst, 1802; Planeustomus Jacquelin du Val, 1857; Styloxys Gozis, 1886 (subfamily Oxytelinae). The genus Philonthus Stephens, 1829 (subfamily Staphylininae) is mentioned as a host only twice, from Poland and Tibet (Lee 2006, Majewski 1994. Peyritschiella protea is widespread in Europe (Santamaría et al 1991), but seldom reported from other continents: Asia (Tibet [Lee et al 2006]), Africa (Algeria [Maire 1920]), and North America (Cambridge, MA, US [Thaxter 1908]).…”
Section: Hesperomyces Virescensmentioning
confidence: 99%